Pelatihan Komputer Dasar Berbasis Microsoft Word dan Excel untuk Peningkatan Administrasi serta Pencatatan Keuangan Sederhana (Dasar Akuntansi) bagi Pengurus Posyandu di Kelurahan Ciketingudik - Reni Suwandi Ade Puspita (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
Posyandu activities require organized administration and accurate documentation, including participant data, monthly reports, and simple financial records. However, many Posyandu administrators still face difficulties in using computers, which results in manual documentation and inefficient reporting. This community service program aimed to improve participants’ basic computer skills and their ability to use Microsoft Word and Microsoft Excel to support Posyandu administration and simple accounting-based financial recording. The training was conducted on May 8, 2026 at the Ciketingudik Village Hall, involving Posyandu chairwomen from several Delima areas and the PKK/PKP leader. The methods applied included lectures, demonstrations, hands-on practice, and direct mentoring. The training covered file and folder management, document preparation using Microsoft Word, and data recapitulation using Microsoft Excel with basic formulas such as SUM and COUNT. The results show that participants were able to create organized digital folders, prepare official invitation letters, build structured data tables, and compile simple cash recapitulation reports. This program contributes to improving transparency, accountability, and professionalism in Posyandu administration.